Perinatal risk factors in ex-preterm and/or low birthweight Colombian young adults (2024)
Background: Advances in neonatal care have increased survival rates for premature or low birth weight (LBW) infants but raised concerns about long-term neurosensory and psychomotor challenges. Objective: to investigate perinatal factors linked to visual and auditory problems in ex-preterm or LBW young adults, assessing their long-term quality of life. Methods: Participants from a 20 year old randomised controlled trial comparing Kangaroo-Mother Care (KMC) to conventional care were re-enrolled. A group of 50 at term individuals without risk factors was assessed as a reference group. Findings: 5.9% of participants had functional visual issues and 8.1% experienced hearing problems. Those with hearing or visual impairments had longer hospital stays and more neonatal complications. Correlations were found between Griffiths auditory sub-scale results at 6 months and long-term auditory outcomes. Only 27.5% of those with deafness had access to cochlear implants or hearing aids, resulting in lower IQ scores, learning difficulties, and increased risk of depression and self-harm. Participants with visual impairments exhibited lower IQ scores, self-esteem, and HOME test acceptance. However, they did not differ from the group with normal vision in terms of quality of life, depression, or attachment scores. All participants, whether they had issues or not, rated their quality of life higher than their parents did. Interpretation: Preterm or LBW infants with visual and hearing deficits are more likely to face cognitive and emotional challenges in adulthood. This study underscores the importance of a multidisciplinary approach to promptly address these vulnerabilities, reducing the risk of long-term neurodevelopmental and functional issues. Funding: The Grand Challenge Canada, Fulbright Colciencias and Colombia Cientifica – Alianza, The World Bank, managed by the Colombian Administrative Department of Science, Technology and Innovation (COLCIENCIAS).